INSIGHTS INTO THE RELATIONSHIP BETWEEN BONE MINERAL DENSITY AND TRABECULAR BONE SCORE AND THEIR PHYSIOLOGICAL CORRELATION WITH BODY MASS INDEX IN POSTMENOPAUSAL WOMEN WITH OSTEOPOROSIS - Almajeed, Mustafa Abd; Ibrahim, Nawal Khalil; Hamdan, Thamer Ahmed (Eastern Ukrainian Medical Journal, 2026)
Background: People with a high body mass index (BMI), are somewhat protected against osteoporosis. Osteoporosis is a complex condition that primarily affects postmenopausal women and causes substantial morbidities and fatalities. Bone mineral density (BMD) evaluates just one of the many factors that affect bone. (TBS) is the trabecular bone score derives from DEXA scan images. It has been noted that there is a positive connection between BMD and a high body mass index (BMI). Objective: This study aims to clarify for present any link between T-score, TBS, BMD, and BMI in postmenopausal women who had suffers from osteoporosis. Methods: 566 postmenopausal women were chosen from the Alzahraa center of the Ibn-Albitar Private Hospital in Basrah, Iraq, for this study. Dual X-ray absorptiometry (DEXA) was used to measure the BMD of the L1–L4 vertebrae, and the TBS iNsight program was used to calculate the trabecular bone score from the same area of the participants' spine. Results: In patients with osteoporosis and low bone density, there was a statistically significant negative connection between TBS and BMI. BMI and TBS did not substantially correlate in patients with normal T-scores (P > 0.01). Additionally, among participating individuals with osteoporosis, there was a noteworthy positive correlation between high BMI and TBS-T-score. Conclusions: Higher BMI was linked to a lower TBS in patients with an aberrant T-score, despite the fact that it had a preventive effect against osteoporosis. However, among patients with normal T-scores, BMI had no discernible impact on TBS.